E-Word of Mouth, Perceived Service Quality, dan Repurchase Intention Konsumen Mixue: Lifestyle sebagai Pemoderasi - Abriandi; Rada Dea Ananda Puspa (Universitas Medan Area, 2023)
The purpose of this study was to analyze the effect of e-word of mouth and perceived service quality on repurchase intention with lifestyle as a moderating variable. Acquisition of respondents as many as 300 people who are customers of Mixue. The sampling technique is purposive sampling which determines the criteria for respondents who are 10-25 years old and have purchased Mixue products more than 1 time. The data processing method uses the help of SmartPLS 4 SEM software. The results showed that e-word of mouth, perceived service quality, and lifestyle had a positive and significant effect on repurchase intention, but lifestyle was not able to moderate the effect of e-word of mouth on repurchase intention and lifestyle was also unable to moderate the effect of perceived service quality on repurchase intentions. This research con-cludes that the owner of the Mixue Indonesia franchise needs to create things that can support fulfilling consumer lifestyles, especially generation Z. In addition, the use of social media in e-word of mouth activities also needs to be increased in an effort to attract consumer repurchase interest. As for perceived service quality, it still needs to be improved.